Causes of accidents on the roads and the development of devices to prevent collisions - Зубенко, Денис Юрьевич (Technology audit and production reserves, 2014)
The statistics of road accidents in the world is presented. The most probable causes and consequences of accidents on roads were analyzed. Devices, allowing to minimize losses in vehicle collisions were proposed. To solve the problem of safe movement of vehicles on roads is the topical issue. For this, it is necessary to study and analyze the statistics of road accidents and to identify the key factors, which cause fatal accidents or injuries. To develop the complex of measures and modern devices, allowing to avoid collisions and minimize losses in accidents is pressing problem. Road accidents are the most dangerous threat to human health around the world. Damage from road traffic accidents (RTA) exceeds the damage from all other transport accidents (aircrafts, ships, trains, etc.) together. Road accidents are one of the major global threats to human health and life. The problem is aggravated by the fact that victims of accidents are as a rule young and healthy (before the accident) people. According to the WHO, in the world 1.2 million people die and about 50 million are injured in road accidents each year. More than 27,000 die on Russian roads, and more than 40,000 on USA roads. In terms of the number of vehicles, these figures mean 70 dead in road accidents in Russia or 15 dead in the USA in a year for each 100 000 vehicles. According to statistical estimates, more than 3 million people died in accidents on U.S. roads since the beginning of the XX century that exceeds all USA losses (650,000) in all military conflicts (since 1774).